ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN KOTA PONTIANAK DALAM MELAKUKAN PEMBELIAN ONLINE - Mu LIANI (Jurnal Ekonomi Integra, 2016)
Consumer behavior in order to obtain a product or service is never the same and always changing time by time. The development of more advanced information technologies, in particular the Internet, changing the way how the consumers shop. Nowadays, Consumers not only shop at the market place but also in the market space or virtual market place like Facebook, Instagram and many other supported websites (Amazone, ebay, Shopee, Elevenia, Dino Market, Berniaga, Kaskus, OLX, etc). The objective of this research was to analyze the influence factors that explain the consumer decision making process in doing online shopping which were done by 19-35 years old respondents in website, market place, Facebook or related websites which sell online.The research used survey method by using questionnaires which involving 100 numbers of respondents in Pontianak City to answer the questions. From the statistics test, the Cronbach’s Alpha for product as X1 was 0.894 from 7 indicators, price as X2 was 0.814 from 7 indicators, promotion as X3 was 0.877 from 6 indicators, trust as X4 was 0.896 from 10 indicators, and psychologies as X5 was 0.806 from 8 indicators . All of them have reached more than the standard table for Cronbach’s Alpha (0,60), it meant all of them were reliable and valid to be analyzed. The final calculation for the double regression showed that the hypotheses were not significantly related for product as X1 (-1,380) and promotion as X3(0,254) because both of the results were lower than 1,992. Different to variable product and promotion, the hypotheses for price as X2 (3,825), trust as X4 (2,448) and psychologies as X5 (2,087)were significantly related because all of them were higher than 1,992. The result’s statements above stated that there was no any influences between product and promotion to consumer decision making because H0 was achieved and H1 was rejected, but there were influence among price, trust and psychologies because H0 was rejected and H1 was achieved where Y = 0,898 + (-0,111) X1 + 0,374 X2 + 0,034 X3 + 0,282 X4 + 0,212 X5